(untitled) (City: History, Culture, Society, 2025)
The article analyses the features of memorialisation of the Anti-Terrorist Operation (ATO) in the urban space of Kryvyi Rih, a major industrial city in southern Ukraine. It examines the establishment of key ATO memorials in Kryvyi Rih and their role as sites for official and public remembrance ceremonies. The focus is also on the interplay between memorial and political contexts and the interaction of grassroots and official initiatives, which has created both "official" and "popular" places of memory. Another key point of discussion is the role of ATO memorials in urban commemorative practices, which extend beyond merely honouring fallen local soldiers who died in the Donbas conflict. The article also addresses the commemoration of the Maidan events in the city, which lacks dedicated memorials. In contrast, the political background of the city’s elites does not align with Maidan values. The study is based on local media reports, district council websites and city information agencies’ websites, and photo and video documentation of commemorative events and memorials in Kryvyi Rih. These sources** thoroughly recorded the history of these memorials and the conduct of remembrance ceremonies. Additionally, the author draws on personal observations of urban commemorative practices from 2014 to 2024. The commemoration of fallen ATO soldiers has become a concern for both the city authorities and various civil society and veterans’ organisations, including groups opposed to the city government. In this context, ATO memorials also serve as sites of Maidan remembrance. This underscores the absolute value of honouring fallen soldiers within Kryvyi Rih’s memorial landscape. While the city administration and opposition groups acknowledge this remembrance as necessary, public commemorations sometimes involve separate initiatives and distinct memory sites to avoid engagement with official events. Moreover, ATO memorials are used for ceremonies related to other significant national dates, demonstrating that remembrance of ATO casualties has become a key symbol of Ukrainian independence.